Fluid consumption habits of elite athletes - Arabaci, R. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
INTRODUCTION: Fluids are a vital requirement for athletes. All nutrients are important for performance, but has a more critical importance of water. Dehydration and hypohidration can lead to headaches, reduced blood volume, reduced endurance, altered thermoregulatory capability and impaired cognitive and physical performance 1-3. To our knowledge, no studies have examined water intake using the most recently available dietary data of Turkish athletes. Objective of present study was to examine fluid consumption habits of elite Turkish athletes and compared total fluid intake of training and non-training days. METHODS: A total of 142 male (mean age 24.5±4.2 years, height 177±11.7 cm and weight 79.1±6.9 kg) and 103 female (mean age 24.8±3.3 year, height 167.6±9.4 cm and weight 58.5±5.6 kg) Turkish elite athletes living in Bursa participated in study. Written questions asked techniques were used for data collection. As data collection tool was administered a questionnaire consisting of two parts. The first part of the questionnaire assessed personal knowledge, the second part assesses water and fluid consumption of subjects. To compare the non-trainng and trainning days fluid consumption was used Independent Samples T Test. RESULTS: Female athletes in non-training (NTD) and training days (TD) intake water 1066.4 ml/day (47.5%) and 1518.4 ml/day (51.4%), tea 386.1 ml/day (17.2%) and 534.7 ml/day (18.1%), fruit juice 175.1 ml/day (7.8%) and 239.3 ml/day (8.1%), energy drinks 40.4 ml/day (1.8%) and 85.7 ml/day (2.9%), respectively. Male athletes in NTD and TD intake water 1192.1 ml/day (48.4%) and 1653.7 ml/day (52.1%), tea 445.8 ml/day (18.1%) and 568.1 ml/day (17.9%), fruit juice 169.9 ml/day (6.9%) and 241.2 ml/day (7.6%), energy drinks 54.2 ml/day (2.2%) and 98.4 ml/day (3.1%), respectively. Statistically significant differences were observe between NTD and TD fluid intake in both gender (p<0.05). Male subjects consumed 28.9% more fluid in TD (3174±46.3) than NTD (2463±32.1 mL/day). Female subjects consumed 31.6% more fluid in TD (2954±35.4) than NTD (2245±45.2 mL/day). DISCUSSION: Adequate fluid consumption, especially water intake is very important for athletes. Athletes have been increased fluid intake in training days. Water is the most increased fluid. This may be related to excessive sweating of athletes during exercise. Drinking sufficient volumes of fluid during physical activity to minimize dehydration is arguably the simplest and most effective means of sustaining physiological function and improving physical performance.